Up-regulated A20 promotes proliferation, regulates cell cycle progression and induces chemotherapy resistance of acute lymphoblastic leukemia cells. Issue 9 (September 2015) - Chen, Shuying; Xing, Haiyan; Li, Shouyun; Yu, Jing; Li, Huan; Liu, Shuang; Tian, Zheng; Tang, Kejing; Rao, Qing; Wang, Min; Wang, Jianxiang
Highlights The protein expression of A20 is upregulated in ALL patients and cell lines. A20 depletion decreases proliferation of ALL cells both in vivo and in vitro. A20 depletion induces cell cycle arrest at G0/G1 stage of ALL cells. A20 depletion increases the sensitivity of ALL cells to chemotherapy. The regulation mechanism of A20 was associated with p-ERK and p53 signal pathways.